Influence of phytocenosis on the medical potential of moss extracts: the Pleurozium schreberi (Willd. ex Brid.) Mitt. case - Grzegorz J. Wolski; Agnieszka Kobylińska; Beata Sadowska; Anna Podsędek; Dominika Kajszczak; Marek Fol (Scientific Reports, 2023)
Abstract The question was asked “whether plant phytocenosis has an impact on the medical potential of the extracts from Pleurozium schreberi”. Moss samples were collected from four different phytocoenoses: mixed forest (oak-pine forest), a forest tract in pine forest, 5–15-year-old pine forest and 50-year-old pine forest. Chemical composition of the extracts, antioxidative capacity (FRAP and ABTS·+ assays), as well as biological activities including cytotoxicity for the mouse fibroblasts L929 line (MTT reduction assay), biostatic/biocidal effect against selected bacteria and fungi (broth microdilution method followed by culture on solid media), and regenerative properties on human fibroblasts HFF-1 line (scratch assay) were tested. The conducted research clearly proves that phytocenosis determines the quality of moss extracts. The analyses showed that in every examined aspect the IV-7 extract (obtained from a specimen collected in a Pinus sylvestris L. forest, monoculture up to 15 years old) exhibited the highest values and the strongest activity. Other extracts of the same species but growing in other phytocenoses—in a mixed forest (IV-5), a forest tract in a Pinus sylvestris monoculture forest (IV-6) and in a P. sylvestris forest of pine monoculture about 50 years old (IV-8) showed much weaker activity and lower values of the above-mentioned parameters. At the same time, none of the tested extracts exerted a pro-regenerative effect. The P. schreberi extracts were characterized by a varied total content of phenolic compounds in the range from 0.63 ± 0.02 to 14.01 ± 0.25 mg/g of plant material. UPLC/MS analysis showed a varied phenolic profile of the extracts, with caffeoylquinic acid and quercetin triglucoside predominating in all of them.